Pengaruh Konsentrasi Gula pada Karakteristik Kimia dan Organoleptik Sari Buah Galoba (Hornstedtia alliacea) - Noija, Rio I; Palijama, Syane; Tetelepta, Gilian (Jurnal Agrosilvopasture-Tech, 2024)
This research aims to determine the appropriate sugar concentration on the chemical and organoleptic properties of galoba fruit juice. The design used was a Completely Randomized Design with four treatment levels of sugar concentration, namely 9%, 11%, 13%, and 15%. The study found that adding 13% sugar concentration was the best method for producing galoba fruit juice, which had the following properties: pH of 3.68, total dissolved solid of 23.53°Brix, total acid of 16.33, vitamin C content of 0,029 mg/100 g, and organoleptic characteristics with the hedonic quality test include slightly cloudy white color, galoba taste, slightly galoba aroma, slightly clear appearance, and overall thethe panelists like the hedonic test variables